2020
DOI: 10.1039/c9sc06574a
|View full text |Cite
|
Sign up to set email alerts
|

Electron-enriched thione enables strong Pb–S interaction for stabilizing high quality CsPbI3 perovskite films with low-temperature processing

Abstract: A neutral molecular additive of 4(1H)-pyridinethione (4-PT) is used for growing high quality black-phase CsPbI3 thin films at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…Possible Pb–S interactions between the perovskite surface and thiophene groups introduced in the HTM structure can lead to beneficial effects, in terms of modified electronic properties, improved charge mobility, and trap passivation in PSCs. [ 11,12 ] This motivated us to investigate the introduction of electron‐rich thienyl units at the periphery of the Ullazine core, either as the sole donor units or as π‐bridges between the Ullazine and additional diarylamine donors. Moreover, the additional installation of peripheral electron‐withdrawing substituents on the planar Ullazine core could provide tunable HOMO–LUMO energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…Possible Pb–S interactions between the perovskite surface and thiophene groups introduced in the HTM structure can lead to beneficial effects, in terms of modified electronic properties, improved charge mobility, and trap passivation in PSCs. [ 11,12 ] This motivated us to investigate the introduction of electron‐rich thienyl units at the periphery of the Ullazine core, either as the sole donor units or as π‐bridges between the Ullazine and additional diarylamine donors. Moreover, the additional installation of peripheral electron‐withdrawing substituents on the planar Ullazine core could provide tunable HOMO–LUMO energy levels.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how CuP functionalizes the perovskite film surface, Raman spectroscopy tests were performed and shown in Figure 2f. The appearance of new peaks for the CuP-treated perovskite sample at 415, 748, and 816 cm −1 assigned to the Pb-S bond [35][36][37] indicates that the thiol in CuP can react with the surficial Pb ion from the perovskite film. It can be concluded that the CuP molecules anchor on the perovskite surface by forming interfacial Pb-S bonds between perovskite and CuP.…”
Section: Perovskite Surface Modification With Cup By Forming Interfacial Pb-s Bondsmentioning
confidence: 99%
“…The use of HI or HPbI 3 as a precursor in the method of obtaining one and two steps, has been shown to improve the stability of the active phase of perovskite CsPbI 3 and allow it to be obtained at lower temperatures [25], XIANG et al, reported obtaining CsPbI 3 using HI as a catalyst, which allowed the generation of stable perovskite for 2 months and 300 hours under irradiation, using carbon as the conductive electrode [98]. In the work reported by XU et al, they use 4 (1H) -pyridinethione as an additive to promote crystallization through the interaction of S-Pb, which allows obtaining this α-cubic perovskite at low temperature (90-100 ° C) and keep it stable for 20 days, with a cell efficiency of 85%, compared to the first day of testing [115].…”
Section: Cspbi3 Perovskitementioning
confidence: 99%